'Green revolution' dwarf gene sd1 of rice has gigantic impact. (30th October 2020) - Gaur, Vikram Singh; Channappa, Giresh; Chakraborti, Mridul; Sharma, Tilak Raj; Mondal, Tapan Kumar
Abstract: Rice ( Oryza sativa L.) is one of the most important cereal that has fed the world over a longer period. Before green revolution, cultivated rice is believed to have consisted of thousands of landraces each adapted to its specific climatic conditions by surviving against different abiotic and biotic selection pressure. However, owing to the low yield, photo-period sensitivity, late maturity and sensitivity to lodging of these landraces grown world-wide, serious concerns of impending global food crisis was felt during the 1960s because of (i) unprecedented increase of the population and (ii) concomitant decline in the cultivable land. Fortunately, high-yielding varieties developed through the introgression of the semi-dwarf1 gene (popularly known as sd1 ) during the 1960s led to significant increments in the food grain production that averted the apprehensions of nearing famine. This historical achievement having deep impact in the global agriculture is popularly referred as 'Green Revolution.' In this paper, we reviewed, its genetics as well as molecular regulations, evolutionary relationship with orthologous genes from other cereals as well as pseudo-cereals and attempted to provide an up-to-date information about its introgression to different rice cultivars of the world.